2021
DOI: 10.3389/fgene.2021.714697
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of N6-Methyladenosine-Related Long Non-Coding RNAs With Tumor Immune Microenvironment and Clinical Prognosis in Lung Adenocarcinoma

Abstract: Background: Lung adenocarcinoma (LUAD) is the major subtype of lung cancer and is associated with very high mortality. Emerging studies have shown that N6-methyladenosine (m6A)-related long non-coding (lnc) RNAs play crucial roles in tumor prognosis and the tumor immune microenvironment (TME). We aimed to explore the expression patterns of different m6A-related lncRNAs concerning patient prognosis and construct an m6A-related lncRNA prognostic model for LUAD.Methods: The prognostic value of m6A-related lncRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 54 publications
2
20
2
Order By: Relevance
“…Lately, studies have found that m 6 A modification could regulate the metabolism of lncRNAs [ 24 , 25 ]. For example, in non-small-cell lung cancer, MeRIP-Seq discovers that there was a m 6 A modification site in ABHD11-AS1 and METTL3 promotes the ABHD11-AS1 transcript stability to increase its expression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lately, studies have found that m 6 A modification could regulate the metabolism of lncRNAs [ 24 , 25 ]. For example, in non-small-cell lung cancer, MeRIP-Seq discovers that there was a m 6 A modification site in ABHD11-AS1 and METTL3 promotes the ABHD11-AS1 transcript stability to increase its expression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to mRNAs, lncRNAs are also abundantly expressed in BC. The chemical internal modification on eukaryotic messenger RNAs dramatically changes the fate of RNAs [ 17 ]. In addition to this, the m 6 A modification on lncRNA also enriches the biological functions of lncRNAs in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt/mTOR signaling pathway was found to be potentially affected by m6A regulators in most cancers such as gastrointestinal cancer ( Zhao Q. et al, 2020 ) and ovarian cancer ( Bi et al, 2021 ), which was consistent with our results. M6A modification of lncRNAs may affect the occurrence and development of tumors, lncRNAs may also target m6A regulators as competitive endogenous RNAs, affecting tumor invasive progression ( Xu F. et al, 2021 ; Zhao et al, 2021 ). Taken together, these findings implied potential correlation between m6A-modified lncRNAs and AML initiation or progression.…”
Section: Discussionmentioning
confidence: 99%
“…The expression and co-expression of m6A-related genes in AML were studied. Next, we calculated the correlation coefficient and p value between m6A-related genes and lncRNA profiles, and m6A-related lncRNAs were identified according to the standard of p < 0.05 in the correlation analysis as mentioned in previous studies ( Zhang P. et al, 2021 ; Zhao et al, 2021 ). Moreover, we incorporated the expression of m6A-related lncRNA in TCGA and the GEO database into model construction.…”
Section: Methodsmentioning
confidence: 99%